Dissipative Structures and Fractal Approach to the Formation of Non-Crystalline States - Mar’yan, M.I.; Yurkovych, N.V. (Physics and Chemistry of Solid State, 2016)
Found that the formation of fractal dissipative structures in non-crystalline solids associated with the creation of self-consistent fields of soft atomic configurations and thermal behavior of such structure-sensitive characteristics that meet the minimum energy dissipation for a given external parameters - speed cooling and process modes receipt. It is shown that this fact makes it possible to determine the non-crystalline structure through the processes of self-organization.